Integrating Faith Values in the Workplace: Enhancing Performance, Commitment, and Psychological Well-Being - Radja Bagus Herlambang; Mutiara Cantika; Sumarta; Hudallah Hudallah (Lentera Peradaban: Journal on Islamic Studies, 2025)
This study explores the integration of spirituality and faith values in the workplace to enhance productivity, psychological well-being, and the quality of interpersonal interactions among employees. The research background arises from the need for modern organizations to combine workplace spirituality with professionalism, enabling employees to have higher intrinsic motivation, stronger commitment, and greater job satisfaction. The study employs a literature review and conceptual analysis using an inductive approach, examining journals, scholarly articles, and books from the past five years. The findings indicate that the consistent application of spiritual practices, including spiritual leadership training, mindfulness, and faith-based employee development, significantly impacts work ethics, employee engagement, and organizational citizenship behavior. Integrating spirituality fosters an inclusive, harmonious, and productive work culture while enhancing psychological well-being and reducing stress. In conclusion, workplace spirituality is not merely a moral dimension but also an effective managerial strategy that supports performance, motivation, and the sustainable competitiveness of organizations.